Multistep energy and electron transfer processes in novel rotaxane donor-acceptor hybrids generating microsecond-lived charge separated states - Kirner, Sabrina; Henkel, Christian; Guldi, Dirk Michael; Megiatto, Jackson D.; Schuster, David I. (Chemical Science, 2015)
A new set of [Cu(phen)2]+ based rotaxanes, featuring [60]-fullerene as an electron acceptor and a variety of electron donating moieties, namely zinc porphyrin (ZnP), zinc phthalocyanine (ZnPc) and ferrocene (Fc), has been synthesized and fully characterized with respect to electrochemical and photophysical properties. The assembly of the rotaxanes has been achieved using a slight variation of our previously reported synthetic strategy that combines the Cu(i)-catalyzed azide-alkyne cycloaddition reaction (the "click" or CuAAC reaction) with Sauvage's metal-template protocol. To underline our results, complementary model rotaxanes and catenanes have been prepared using the same strategy and their electrochemistry and photo-induced processes have been investigated. Insights into excited state interactions have been afforded from steady state and time resolved emission spectroscopy as well as transient absorption spectroscopy. It has been found that photo-excitation of the present rotaxanes triggers a cascade of multi-step energy and electron transfer events that ultimately leads to remarkably long-lived charge separated states featuring one-electron reduced C60 radical anion (C60-) and either one-electron oxidized porphyrin (ZnP+) or one-electron oxidized ferrocene (Fc+) with lifetimes up to 61 microseconds. In addition, shorter-lived charge separated states involving one-electron oxidized copper complexes ([Cu(phen)2]2+ (τ < 100 ns)), one-electron oxidized zinc phthalocyanine (ZnPc+; τ = 380-560 ns), or ZnP+ (τ = 2.3-8.4 μs), and C60- have been identified as intermediates during the sequence. Detailed energy diagrams illustrate the sequence and rate constants of the photophysical events occurring with the mechanically-linked chromophores. This work pioneers the exploration of mechanically-linked systems as platforms to position three distinct chromophores, which are able to absorb light over a very wide range of the visible region, triggering a cascade of short-range energy and electron transfer processes to afford long-lived charge separated states.
CRIS-Team Scopus Importer:2023-03-07